Evaluation of Mechanical Properties and Water Resistance Performance of Concrete Modified with Graphene Nanoplatelets (GNP) - Leidys Johana Jaramillo; Robin Kalfat (International Journal of Concrete Structures and Materials)
Abstract Nano materials made from graphene have emerged as highly effective additives that can significantly improve the engineering properties of cement-based composites. This research investigated the impact of adding graphene nanoplatelets (GNP) on the performance of concrete, using both sonicated and non-sonicated GNP dispersions. The study evaluated fresh concrete properties through slump tests, and mechanical characteristics were analyzed at 7, 14, and 28 days by conducting tests for compressive, flexural, and tensile strength. Homogeneity was assessed using ultrasonic pulse velocity (UPV), while durability was evaluated by examining water absorption (Ai), apparent volume of permeable voids (AVPV), and sorptivity. Furthermore, scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) were employed to study how GNP affected the microstructure of concrete. The research found that the most significant improvements in engineering properties occurred when sonicated GNP dispersions were added at a concentration of 0.25 wt%. This addition resulted in enhancements of compressive, flexural, and tensile strengths by 20.8%, 10.5%, and 11.4%, respectively, at 28 days. UPV also improved by 12.9% at the same GNP concentration. Furthermore, Ai, AVPV, initial sorptivity, and secondary sorptivity decreased by 28.3%, 26.3%, 22%, and 27%, respectively, at 28 days. Microscopic analysis indicated that GNP contributed to reinforcing the microstructure of concrete through nucleation and filling effects, thereby enhancing the material's overall engineering performance.